The Mediation Role of Earnings Management on the Effect of Disclosure of Corporate Social Responsibility on Financial Performance - Aristi Prita Isywara; Yeney Widya Prihatiningtias; Arum Prastiwi; Nanik Wahyuni (Postgraduate Program Merdeka University, 2024)
This study aims to analyze the effect of corporate social responsibility disclosure on financial performance through earnings management. This study develops agency theory and proves the relationship between CSR, earnings management and financial performance variables. Indicators of corporate social responsibility variables are social, economic, environmental, human rights, as well as employment practices and work convenience. Indicators of financial performance variables are Return on Equity (ROE) and Return on In-vestment (ROI). Earnings management variable indicators use the formula approach from Kothari. The research design uses a causality explanation. The population in this study are all mining companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The sampling method used is a census with a total of 50 samples. Data analysis used multiple regression methods. The results of this study indicate that corporate social responsibility has a negative effect on financial performance with ROI indicators and earnings management can mediate the effect of corporate social responsibility on financial performance with ROI indicators. JEL Classification: G32; Q56; M14; L25 DOI: https://doi.org/10.26905/afr.v7i3.13174